2013
DOI: 10.2478/romneu-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic extracerebral fluid collections

Abstract: Objective: Posttraumatic extracerebral fluid collections represent a heterogeneous group of conditions that have different terminologies but the same clinical and imaging features, benefiting from the same therapeutic modalities. Between hygroma/hydroma and serous meningitis there is only a topographic difference that has no influence regarding the therapeutic decision or the patient’s outcome. Posttraumatic extracerebral fluid collections present themselves as a unitary group which benefits from a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For different authors, subdural hygroma is more prevalent in older patients with some degree of cerebral atrophy [14] [15].…”
Section: Discussionmentioning
confidence: 99%
“…For different authors, subdural hygroma is more prevalent in older patients with some degree of cerebral atrophy [14] [15].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, present work considered patients who underwent surgery due to subdural hygroma. Studies have revealed that subdural hygroma is mainly noted in old patients (17,18,19,20).…”
Section: Disscussionmentioning
confidence: 99%